Motor Competence in Early Childhood Is Positively Associated With Bone Strength in Late Adolescence. (6th February 2016) - Ireland, Alex; Sayers, Adrian; Deere, Kevin C; Emond, Alan; Tobias, Jon H
ABSTRACT: The onset of walking in early childhood results in exposure of the lower limb to substantial forces from weight bearing activity that ultimately contribute to adult bone strength. Relationships between gross motor score (GMS), at 18 months and bone outcomes measured at age 17 years were examined in 2327 participants in the Avon Longitudinal Study of Parents and Children (ALSPAC). Higher GMS indicated greater motor competence in weight‐bearing activities. Total hip bone mineral density (BMD) and hip cross‐sectional moment of inertia (CSMI) were assessed from dual‐energy X‐ray absorptiometry (DXA). Bone measures including cortical bone mineral content (BMC), periosteal circumference (PC), cortical thickness (CT), cortical bone area (CBA), cortical BMD (BMDC ) and cross‐sectional moment of inertia (CSMI) were assessed by peripheral quantitative computed tomography (pQCT) at 50% distal‐proximal length. Before adjustment, GMS was associated with hip BMD, CSMI, and tibia BMC, PC, CT, CBA and CSMI (all p < 0.001) but not BMDC ( p > 0.25). Strongest associations (standardized regression coefficients with 95% CI) were between GMS and hip BMD (0.086; 95% CI, 0.067 to 0.105) and tibia BMC (0.105; 95% CI, 0.089 to 0.121). With the exception of hip BMD, larger regression coefficients were observed in males (gender interactions all p < 0.05). Adjustment for lean mass resulted in substantial attenuation of regression coefficients, suggesting associations between impaired motor competence and subsequent bone development are partly mediated by alterations in body composition. In conclusion, impaired motor competence in childhood is associated with lower adolescent bone strength, and may represent a risk factor for subsequent osteoporosis. © 2015 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research (ASBMR).